The Relationship of Gastrointestinal Disorders to Malnutrition in Children with Cerebral Palsy in the WKCP Community (Wahana Keluarga Cerebral Palsy) Yogyakarta, Indonesia - Gina Puspita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: One of the causes of malnutrition that often occurs is gastrointestinal disorders. The existence of anatomical and physiological abnormalities in the gastrointestinal tract is the main cause. This study aimed to assess the relationship between gastrointestinal disorders and the incidence of malnutrition in children with cerebral palsy in the WKCP community Yogyakarta, Indonesia. Methods: A cross-sectional analytic observational study involving 20 cerebral palsy subjects who met the inclusion and exclusion criteria. The data collection technique is by consecutive sampling. The type of data used in the research uses a questionnaire gastrointestinal symptoms rating scale (GSRS). Data status anthropometry has also been collected. Data analysis using SPSS with chi-square. Results: The mean age of the subjects was 8.9 ± 4.1 years. The male gender (60%) is greater than the female. The comparison of good nutritional status and malnutrition is not much different, namely 55%:45%, respectively. The percentage of children experiencing severe gastrointestinal symptoms is 25%. The most common gastrointestinal disorders are constipation (65%) and upper dysmotility disorders (60%). In the results of this study, there was no relationship between gastrointestinal disorders and the incidence of malnutrition (p=0.069). Conclusion: In this study, there was no significant relationship between gastrointestinal disorders and malnutrition in children with cerebral palsy. However, gastrointestinal disorders increase the morbidity and mortality of children with cerebral palsy, so it must be an important concern.